2022
DOI: 10.14309/ajg.0000000000002008
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis on the Effects of Lactulose and Rifaximin on Patient-Reported Outcomes in Hepatic Encephalopathy

Abstract: INTRODUCTION:Patients with hepatic encephalopathy (HE) suffer from significant symptoms and impaired quality of life. Improved understanding on the potential benefits of first-line HE therapies may aid patient-provider discussions regarding expected benefits of HE treatments. We aimed to perform a systematic review to assess the effects of lactulose and rifaximin on patient-reported outcomes (PROs).METHODS:We searched MEDLINE, EMBASE, and Cochrane Library databases for randomized trials or prospective cohort s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 52 publications
0
12
0
2
Order By: Relevance
“…Compared with placebo, lactulose was associated with reduced recurrent overt hepatic encephalopathy (25.5% vs 46.8%) in a meta-analysis of RCTs enrolling 1415 patients with hepatic encephalopathy . In a meta-analysis of 3 clinical trials of 126 participants receiving lactulose, lactulose was associated with an improvement of 6.92 (95% CI, 6.66-7.18) in the Sickness Impact Profile (ranges from 0 [best] to 68 [worst]; clinically important differences are >4) . In a 6-month placebo-controlled, double-blind RCT, rifaximin reduced hospitalization for hepatic encephalopathy from 22.6% to 13.6% among 299 patients with prior hepatic encephalopathy taking lactulose .…”
Section: Discussionmentioning
confidence: 99%
“…Compared with placebo, lactulose was associated with reduced recurrent overt hepatic encephalopathy (25.5% vs 46.8%) in a meta-analysis of RCTs enrolling 1415 patients with hepatic encephalopathy . In a meta-analysis of 3 clinical trials of 126 participants receiving lactulose, lactulose was associated with an improvement of 6.92 (95% CI, 6.66-7.18) in the Sickness Impact Profile (ranges from 0 [best] to 68 [worst]; clinically important differences are >4) . In a 6-month placebo-controlled, double-blind RCT, rifaximin reduced hospitalization for hepatic encephalopathy from 22.6% to 13.6% among 299 patients with prior hepatic encephalopathy taking lactulose .…”
Section: Discussionmentioning
confidence: 99%
“…Its determinants are complex and related to disease severity, comorbidities, the home environment, medication burden, and symptom burden 1,2,19 . Prior studies have demonstrated that lactulose therapy can improve HRQOL in patients with HE, both overt and covert 6 . In practice, clinicians often initiate lactulose therapy for poor PROs that are linked to HE, such as poor HRQOL, poor sleep, and depressive symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Sleep disorder in cirrhosis is also a complex topic with multiple contextual nuances, and the field is evolving. For example, lactulose therapy improves sleep for patients with covert hepatic encephalopathy . Following the publication of our Review, we showed that many patients with cirrhosis experienced improved sleep with use of lactulose even if they had not been diagnosed with hepatic encephalopathy …”
mentioning
confidence: 82%